Analisis High Order Thinking Skill (HOTs) pada Tujuan dan Asesmen Mata Pelajaran Kimia - Dinyah Rizki Yanti Zebua; Harmalis Harmalis (Journal on Education, 2021)
The purpose of this study was to analyze the High Order Thinking Skill (HOTS) on learning purposes and assessments as well as the suitability of HOTS on the learning purposes and assessments in the Chemistry subject especially on Acid and Basa Concept. This research was classified as qualitative research with content analysis. Content analysis is a research method that discusses in depth the contents of written or printed information in a mass media. The informant of this research is the document of the Learning Implementation Plan and daily test questions obtained from the Chemistry teachers at SMA Negeri 2 Sungai Penuh. The results of this study were (1) HOTS has been contained in the learning purposes of chemistry in the Acid and Basa Concept at SMA Negeri 2 Sungai Penuh, among the 7 learning purposes, just 4 of them are learning purposes that contain HOTS; (2) HOTS has been contained in the Chemistry Learning Assessment in the Acid and Basa Concept at SMA Negeri 2 Sungai Penuh. There was only one assessment question that contains the HOTS; and (3) there was no relevance between the HOTS that contained in the learning purposes and assessment on the Acid and Basa Concept at SMA Negeri 2 Sungai Penuh.